The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.3312/jyio1952.34.257
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Areas and Roost Utilization of Non-territorial Individuals of the Carrion Crow Corvus corone

Abstract: Abstract.The Carrion Crow Corvus corone has two distinct social types: territorial pairs and flocks of non-territorial individuals.The foraging area and roost utilization of territorial and non-territorial individuals were studied in Ina Basin from 20 March 1992 to 31 December 1993. To study behavior at the individual level, I banded 96 non-territorial birds (1 year old=30, over 2 years old=66) and in addition attached radio transmitters to 10 of them. Territorial individuals defended their territories with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Third, non-territorial adults assembled in the spring roost. Yoshida (2003) found that non-territorial individuals live in flocks until they can acquire a breeding territory, and the flock is composed of juveniles and individuals over two years old. Only rarely are females with developed oviducts non-territorial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, non-territorial adults assembled in the spring roost. Yoshida (2003) found that non-territorial individuals live in flocks until they can acquire a breeding territory, and the flock is composed of juveniles and individuals over two years old. Only rarely are females with developed oviducts non-territorial.…”
Section: Discussionmentioning
confidence: 99%
“…Second, individuals that failed in breeding assembled in the spring roost because they did not need to protect eggs and nestlings. The Carrion Crow has two distinct social types: territorial pairs, and flocks of non-territorial individuals (Yoshida 2003). Pairs breed in territories (Nakamura 1998;Yoshida 2003), thus, sexually mature individuals that bred near the spring roost and failed in breeding must have had territories.…”
Section: Discussionmentioning
confidence: 99%
“…2). It is unclear whether the decrease in roost size resulted from the disturbance, because spring roost size fluctuates from day to day (Yoshida 2003) and usually decreases as the season progresses (Hirabayashi 1962, Kurata & Higuchi 1972, The Roost Research Group 1986, Koshio et al 1996, Nakamura 2003, Yoshida 2003. Crows had used only site A as a roost before the felling of the forest.…”
mentioning
confidence: 99%